P172 Training nurses in sampling and acquisition of specimen during EBUS guided transbronchial needle aspiration. (12th November 2015) - Johnson, V; Stables, W; Binu, S; Smyth, C; Walshaw, M; Mohan, K
Abstract : Introduction: EBUS has now become the standard of choice for mediastinal staging and in the diagnosis of paratracheal and peribronchial lesions. EBUS is usually performed as a 2 person procedure, one to locate and align the bronchoscope and a second to carry out node sampling. Whilst these have traditionally both been medical personnel, with the increase in use of this procedure and alterations in the training and availability of medical staff, we wished to look at the feasibility of empowering nurses to perform needle aspiration during EBUS. Methods: We provide a regional service for EBUS, carrying out over 420 procedures per year, often in technically difficult cases where local hospital EBUS has been unhelpful. From January 2015 we trained a band 5 registered nurse in needle aspiration, who randomly assisted in the procedure in 93 of 172 cases up to June 2015. We report our experience in these 93 cases. Results: These 93 patients were referred from 12 hospitals and 20 had undergone previous undiagnostic procedures (6 EBUS, 14 bronchoscopy). The mean age was 67 years (range 27 – 87) and 50 were male. 82 were performed under local anaesthesia using lignocaine spray and intravenous midazolam (1 – 10 mg; mean 4 mgs) and the remaining 11 under general anaesthesia. 200 lymph nodes (2R, 4R, 4L, 7, 10R, 10L, 11R) and 13 lung lesions were biopsied. Results were as follows: Adequate samples were obtained in 99% (91/93) and the NSCLC - NOS rate was 2%. 31 adenocarcinoma, 10 squamous cell carcinoma, 10 small cell carcinoma, 1 NSCLC - NOS, 1 large cell neuroendocrine carcinoma, 1 soft tissue lesion (repeat EBUS showed myxoid spindle cell mesenchymal lesion), 1 breast carcinoma, 19 nonspecific benign nodes, 15 sarcoid and 2 TB. There were no complications. Conclusion: Our findings suggest that with motivated staff and adequate training, it is possible for nurses to perform needle aspiration during EBUS procedure with excellent results. This could be adopted as the method of choice by other centres as EBUS services continue to expand.